Synthesis, characterization, biological activities and molecular docking of Epilobium parviflorum aqueous extract loaded chitosan nanoparticles - Egil, Abdurrahim Can; Ozdemir, Burak; Gok, Bahar; Kecel-Gunduz, Serda; Budama-Kilinc, Yasemin (ELSEVIER, 2020)
Epilobium is a medicinal plant; its extracts are widely used traditional medicine due to their broad range of pharmacological and therapeutic properties. Its most prominent feature is its therapeutic effects on prostatic diseases. The aim of this study is preparation of controlled release system of Epilobium parviflorum, and determination of its potential of anticancer applications. For this purpose, Epilobium parviflorum extract (EPE) loaded chitosan nano particles were prepared with ionic gelation method to increase the bioavailability of the extract. The nanoparticles were investigated in terms of size, zeta potential, polydispersity index, encapsulation efficiency, loading capacity and release profile. Besides, scanning electron microscopy (SEM) was used to observe the morphology of the nanoparticles. Moreover, Ames/Salmonella test was used to determine the mutagenicity of EPE, and it was shown that it had no mutagenic effect. It was found that EPE loaded chitosan nanoparticles were with 64.47 nm in average size, 0.168 PdI and 15.2 mV zeta potential. Encapsulation efficiency and loading capacity were found as 92.46% and 8%, respectively. Finally, DNA binding assay and in silico molecular docking studies were performed between EPE and DNA in order to contribute to design of plant based controlled release system for use in cancer therapy. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: Chitosan; Epilobium parviflorum; Nanoparticles; Encapsulation; Nanotechnology; Molecular docking; DNA binding; AMES TEST; MUTAGENICITY; ANTIOXIDANT; WATER; GENOTOXICITY; Biochemistry & Molecular Biology; Chemistry; Polymer Science